Innovation, creativity and governance: Social dynamics of economic performance in city-regions. Issue 4 (1st October 2016) - Wolfe, David; Bramwell, Allison
Abstract : The pressure towards a globalizing, knowledge-based economy raises questions about the underlying determinants of economic performance in city regions. The creation and diffusion of new knowledge drives innovation in knowledge-intensive production and service activities, which in turn, drives economic performance and growth. Although these processes are strongly shaped by national institutions and global knowledge flows, recent analyses of innovation and creativity emphasize the continuing relevance of regions in general and urban regions in particular as critical sites for determining economic performance. This work also suggests that the underlying social dynamics of urban regions are particularly significant in shaping economic outcomes. This paper explores some recent evidence on the social nature of innovation dynamics in urban regions, the increasing significance of talent and creativity in urban economies and their implications for the economic performance of city regions. It concludes with a discussion of the need for the strategic management of urban economies to cope with the challenges they face.